OLAHRAGA DAN PERUBAHAN SOSIAL: KAJIAN LITERATUR DALAM PERSPEKTIF SOSIOLOGI OLAHRAGA - Yonatan Aritonang, Haposan; Siahaan, Mangasi; Aldo Rahmat Pakpahan; Indra Siregar, Yan; Arima, Putra; Natalia Tambunan, Indry; Sitohang, Tulmok; Siagian, Josua (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sport is an important part of society that has a close relationship with social change. The development of modern sports not only functions as a physical activity for health and achievement, but also as a social phenomenon that influences interaction patterns, lifestyles, social solidarity, and community identity. This study aims to analyze the relationship between sports and social change from the perspective of sports sociology. The research method used is a literature review with a qualitative descriptive approach. Data were obtained from various scientific sources such as books, journals, articles, and academic references related to sports and social change. The results of the study indicate that sports play an important role as agents of social change through the formation of discipline, cooperation, sportsmanship, and social solidarity values. In addition, the development of technology and social media has also influenced changes in sports culture in modern society. Sports also contribute to the formation of healthy lifestyles and social identities within society. However, the development of modern sports also creates negative impacts such as the commercialization of sports, excessive fanaticism, and social inequality in access to sports facilities. Therefore, sports have a significant influence on the dynamics of social change in modern society.